On quasi-lamb waves in the system "ideal fluid half-space — elastic layer with initial stresses" - Bahno, O.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
The dispersion curves of normal quasi-Lamb waves in a hydroelastic system are constructed over a wide range of frequencies, by using the three-dimensional linearized equations of elasticity theory of finite deformations for a solid body and the three-dimensional linearized Euler equations for an ideal compressible fluid. The influence of initial stresses in the pre-deformed elastic layer and of the half-space of an ideal compressible fluid on the phase velocities of quasi-Lamb waves in a hydroelastic waveguide is analyzed. The numerical results are presented in the form of graphs, and their analysis is given.